CHANGES IN NEAR-SURFACE WIND SPEED IN THE SOUTH OF BENIN FROM 1961 TO 2016 - HOUNGNINOU, BODOUN ETIENNE; ALLE, C. S. ULRICH; GUEDJE, K. François; KOUGBEAGBEDE, Hilaire (My University, 2017)
The trends of changes in the near-surface wind speed from 1961 to 2016 in the South of Benin have been analyzed based on anemometric data of the synoptic station in Cotonou. From the linear regressions and the application of Pettitt test, the decennial and interannual variabilities of the monthly and yearly average speeds have been analyzed. The results show a strong decrease of the wind between 1961 to 1977 and less between 1978 and 2008. Starting in 2009, the wind speeds increased due to the intensification of the wind during the first half of the year except for February. The changes in wind speed are mainly due to strong winds fluctuations.
Keywords: wind speed; climate change; Beaufort’s; scale; West Africa; Benin